Why not to avoid the smell of danger? Unexpected behavior of the Cypriot mouse surviving on the island invaded by black rats. Issue 4 (1st August 2015) - Frynta, Daniel; Baladová, Margaréta; Eliášová, Barbora; Lišková, Silvie; Landová, Eva
Abstract: Mus cypriacus is a recently discovered endemic species that evolved about half a million years ago on the Cyprus Island in an absence of most mammalian predators and competitors. As on other Mediterranean islands, the faunal composition was dramatically changed by the invasion of commensal and domestic species following Holocene colonization by humans. We examined the behavioral responses of the Cypriot mouse to the odors of these new competitors (black and Norway rat, house mouse and spiny-mouse) and predator (domestic cat) as well as controls (Herb-field mouse, guinea pig). We compared them with those of mainland population of house mouse from Syria with different coexistence history. Surprisingly, the Cypriot mouse failed to avoid the odor of its current main competitor, the black rat. Moreover, the response patterns of both the Cypriot and Syrian house mice to the examined odor sources appeared fairly comparable. There was a clear tendency to prefer odors of other murids over unscented sawdust as well as to avoid the odor of a domestic cat. In conclusion, neither the long-term isolation from predators nor the recent strong competition with black rats affected mice competitory and antipredatory responses fundamentally.